Behavioural Assessment Perspective on Reward System Management and Performance: An Empirical Finding on Indonesian Lecturer - Wahyono, Wahyono; Prihandono, Dorojatun; Wijayanto, Andhi (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
The role of this research is to get a clearer picture of how remuneration system influence lecturer and employee performance moderates by motivation, specifically in the state universities. This study commenced in 3 major state universities in Central Java Indonesia in order to have Structural Equation Modelling (SEM)Ã‚Â method was applied to examine and analyse the relationships between determinants.Ã‚Â The results of this study show that Ã¢â‚¬Ëœperformance feedbackÃ¢â‚¬â„¢ has negative effect on Ã¢â‚¬ËœcompetenceÃ¢â‚¬â„¢; the relationship between Ã¢â‚¬ËœcompetenceÃ¢â‚¬â„¢ and Ã¢â‚¬ËœmotivationÃ¢â‚¬â„¢ is negative;Ã¢â‚¬ËœremunerationÃ¢â‚¬â„¢ positively affects Ã¢â‚¬ËœmotivationÃ¢â‚¬â„¢; the greater the level of remuneration, the greater the level of working performance intention in the institutionsÃ¢â‚¬â„¢;and there is positive and significant relationship between Ã¢â‚¬ËœmotivationÃ¢â‚¬â„¢ and Ã¢â‚¬Ëœperformance intentionÃ¢â‚¬â„¢. The study provides the importance of how the remuneration system can be applicated as one focal scheme to enhance instituions performance in general, especially applied to college.